Memory characteristics studies for large deflections in amorphous polymers: Experiments and numerical simulation. (May 2016) - Sujithra, R; Srinivasan, MS; Arockiarajan, A
In this work, the shape memory behaviour for large deflections in a ring-shaped epoxy-based shape memory polymer specimen is studied. A thermo-mechanical test setup was built to study the memory characteristics of ring shaped specimens with three different ratios of epoxy resin and hardener. Thermo-mechanical characterizations were also carried out to understand the material behaviour during shape fixing and recovery phases and also to obtain the material parameters for numerical simulations. Numerical simulations are carried out using a model proposed earlier by the authors based on the theory of multiple natural configurations and implemented using the VUMAT feature of ABAQUS commercial software. The simulation results for free shape recovery and constraint load recovery for large deflections confirm that the model performs well especially in relation to the memory dependent characteristics.